Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/cpe.4790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of node centrality for IoT device selection in opportunistic networks: A comparison study

Abstract: Summary Opportunistic networks (Oppnets) are a subclass of delay‐tolerant networks where communication opportunities (contacts) are intermittent and there is no need to establish an end‐to‐end link between communication nodes. The Internet of Things (IoT) presents the notion of large networks of connected devices, sharing data about their environments and creating a diverse ecosystem of sensors, actuators, and computing nodes. IoT networks consist of heterogeneous collections of resource constrained nodes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, the method of selection in IoT technology, whenever a need, is effective for the effective performance results and always give auspicious results. Similarly, [4] studied and proposed a new technique to overcome the problem of multiobjective optimization in the IoT network. However, their study is mainly based on the selection technique for the selection of QoS aware service in the IoT network environment.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the method of selection in IoT technology, whenever a need, is effective for the effective performance results and always give auspicious results. Similarly, [4] studied and proposed a new technique to overcome the problem of multiobjective optimization in the IoT network. However, their study is mainly based on the selection technique for the selection of QoS aware service in the IoT network environment.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, in 2018, Cuka at el. [4] studied the IoT device selection in the opportunistic network environment, and it is evident that due to the wireless connection between smart devices in an opportunistic network, the routing task is a very challenging problem in this network. However, their study showed that the base station is carried great for longdistance routing in this network environment.…”
Section: Introductionmentioning
confidence: 99%
“…Fuzzy sets and fuzzy logic have been developed to manage vagueness and uncertainty in a reasoning process of an intelligent system such as a knowledge based system, an expert system or a logic control system. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] In this work, we use fuzzy logic to implement the proposed system.…”
Section: Fuzzy Implementationmentioning
confidence: 99%
“…We have implemented fuzzy logic in the area of actor selection for WSAN. Fuzzy logic uses an approximation approach for decision making [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Implementation Of Fuzzy Logicmentioning
confidence: 99%